Analysis of E-Marketing Strategy and Business Innovation in Optimizing Improvement of Service Quality and Its Effect on MSME Income (ADI Journal on Recent Innovation (AJRI), 2024)
This research aims to analyze e-marketing strategies along with business innovations that can optimize improvements in service quality and their impact on the income of Micro, Small and Medium Enterprises (MSMEs). Improvements in information technology and the internet have changed the way MSMEs run their businesses. The research method used in this research is a survey method, by collecting data from MSME business people through questionnaires related to the use of e-marketing and business innovation in improving service quality and MSME income.The results of this research show that the use of e-marketing strategies, such as creating websites, marketing via social media, and using online advertising, contributes positively to increasing sales and business exposure for MSMEs. Apart from that, business innovation, such as new product development and market expansion, also has a significant influence on service quality and increasing MSME income.This research also found that improving the quality of MSME services, such as good customer service and fast delivery, has a positive impact on customer satisfaction and customer loyalty. This then contributes to increasing MSME income. In the context of MSMEs, the use of e-marketing strategies and business innovation are important factors in improving service quality and income. By adopting the right e-marketing strategies and business innovation, MSMEs can expand their market reach, increase customer satisfaction, and ultimately increase revenue.E-marketing strategies and business innovation have a significant influence on improving service quality and MSME income. This research provides recommendations to MSMEs to adopt e-marketing strategies and business innovation in an effort to optimize improvements in service quality and increase income.